Hubungan antara Gaya Kepemimpinan Kepala Sekolah dan Komunikasi antar Pribadi Guru dengan Kinerja Guru di SD DDI Tolai - Fatmawati, Fatmawati (Jurnal Paedagogy, 2020)
With good teacher performance, a quality teaching-learning process will be created. To form a teacher who has good performance, it is needed a Principal who is able to apply his leadership style according to the situation and different levels of ability and experience of the teacher. With the suitability of the Principal's leadership style with the situational, will create a good interpersonal communication between the teacher. By using the classroom action research method to determine the relationship of the teacher leadership style, and communication to the teacher's performance the results are obtained: (a) There is a positive relationship between the Principal's Leadership Style and the teacher's performance at SD DDI Tolai Torue. This is evident from the results of the first hypothesis test with product moment correlation analysis which obtains the price rx1y> rtable (50; 0.01)> rtable (50; 0.05) = 0.472> 0.361> 0.279. (b) There is a positive relationship between Teacher's Interpersonal Communication with Teacher Performance in Tolai Torue DDI Elementary School. This is evident from the results of the second hypothesis test with product moment correlation analysis that obtained rx1y> rtable (50; 0.01)> rtable (50; 0.05) = 0.418> 0.361> 0.279, (c) There is a positive relationship between Leadership Styles Principal and Interpersonal Communication Teachers with Teacher Performance at SD DDI Tolai Torue. This is evident from the results of hypothesis testing with regression analysis of two predictors that obtain Freg> Ftable (2; 47; 0.01)> Ftable (2; 47; 0.05) = 0.913> 5.08> 3.21. (D ) The Principal Leadership Style Variable contributes 59.2% relative and 17.6% effective contribution. While the variable Interpersonal Communication Teachers made a relative contribution of 40.8% and an effective contribution of 12.1%. So it can be seen that the Principal's Leadership Style has a closer relationship with Teacher Performance compared to Teacher Interpersonal Communication variables.